2021
DOI: 10.1136/bcr-2021-246413
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal varices: an atypical cause of globus

Abstract: Laryngeal varices are rare and are usually associated with vocal cord trauma secondary to excessive use of voice. This report is the first documented case of laryngeal varices secondary to thyroid goitre. This is a report of an 83-year-old woman with a known retrosternal goitre chiefly with symptoms of globus. Retrosternal goitre was found to be compressing the pharyngeal venous plexus causing laryngeal venous structures bilaterally to be engorged along the aryepiglottic folds, arytenoids, posterior commissure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…In 10 of those 12 cases, excluding one case treated using esophageal balloon tamponade 10 and one case treated with sclerotherapy 16 , the varices resolved after thyroidectomy. Similar to the present case, there is also report of downhill varices that was detected without bleeding 20 .…”
Section: Discussionsupporting
confidence: 90%
“…In 10 of those 12 cases, excluding one case treated using esophageal balloon tamponade 10 and one case treated with sclerotherapy 16 , the varices resolved after thyroidectomy. Similar to the present case, there is also report of downhill varices that was detected without bleeding 20 .…”
Section: Discussionsupporting
confidence: 90%
“…While it had been previously reported that this syndrome was more often associated with malignancy, this remains unproven 21 . Isolated dysphagia is also possible in case of goiter growing only in the retro-esophageal plane 32,33 , while the only presenting symptom may also be represented by oropharyngeal bleeding because of pharyngolaryngeal "downhill" (i.e ., without venous portal hypertension) varices 34 . Furthermore lower and upper extremities edema 35 , pericardial effusion, chylothorax, or hemoptysis because of tracheal varices have been also described 21 .…”
Section: Clinical Presentationmentioning
confidence: 99%